Analysis of the Effect of Changes in the Implementation of Electronic Medical Records on Organizational Commitment and Employee Performance Mediated by Job Satisfaction (Pusat Riset dan Inovasi Nasional, 2025)
The digital transformation through the implementation of Electronic Medical Records (EMR) is an important innovation in hospital information systems aimed at improving work efficiency, service quality, and administrative management. Nevertheless, the success of EMR implementation is strongly influenced by human factors, particularly job satisfaction and employees’ emotional attachment to the organization. Understanding employees’ responses to EMR-related changes is therefore essential to ensure successful organizational transformation in hospitals. This study employs a quantitative explanatory approach using Partial Least Squares–Structural Equation Modeling (PLS-SEM), supported by qualitative data obtained through interviews. The research population consists of all laboratory employees at Sultan Imanuddin Regional General Hospital (RSUD Sultan Imanuddin) Pangkalan Bun, selected using a purposive sampling technique. The research instruments were developed based on human resource management and health information system theories and include four main variables: changes in EMR implementation, job satisfaction, organizational commitment, and employee performance. The results indicate that changes in EMR implementation have a direct positive effect on job satisfaction and employee performance. Meanwhile, the influence of EMR on organizational commitment occurs indirectly through job satisfaction as a mediating variable, highlighting the central role of job satisfaction in linking digital transformation with organizational commitment. Furthermore, job satisfaction positively affects both organizational commitment and employee performance. These findings demonstrate that successful EMR implementation depends not only on technological aspects but also on human resource readiness, satisfaction, and commitment, which are key drivers of performance improvement and service quality in the digital era of hospital management.